Habilidades sociales en estudiantes del sexto ciclo de secundaria en el área de ciencias sociales en la Institución Educativa N° 60528 Hermanos Palla, Intuto Loreto 2021 - Coelho Napiama, Sara Elizabeth (2022)
The purpose of the research was to determine the level of social skills in students of the sixth cycle of secondary school in Social Sciences in the Educational Institution No. 60528 Hermanos Palla located Intuto district, Loreto in 2021. The investigation was of descriptive type and its design was cross-sectional, field and univariate. The population consisted of 146 social science students, also being the convenience sample. The technique used was the survey and a questionnaire as an instrument to obtain data, the instrument was previously validated by expert judgment. The results of the research show that the level of social skills in students of the sixth cycle of secondary school in Social Sciences in Educational Institution No. 60528 Hermanos Palla is good at 90.6% while it is regular at 9.4%.